Quantifying environmental impact: carbon emissions analysis of cut and fill work in construction - Keintjem, Militia; Suwondo, Riza; Suangga, Made; Juliastuti, Juliastuti; Anda, Martin (Universitas Mercu Buana, 2024)
The construction industry plays a pivotal role in global development, but it also significantly contributes to carbon emissions, necessitating urgent measures to mitigate its environmental impact. The main objective of this research is to analyse and estimate the carbon emissions resulting from cut and fill work in construction projects. This research conducted three comprehensive case studies focusing on heavy equipment excavation, material transport, material spreading, and compaction stages in the construction industry to analyse carbon emissions. The findings reveal that material transport emerges as a prominent source of CO2 emissions within the construction life cycle. This underscores the urgent need for transformative measures to optimize transportation logistics and adopt eco-friendly alternatives, such as electric or hybrid vehicles, for material transport. Additionally, the study highlights the importance of integrating intermodal transportation options to maximize efficiency while minimizing emissions during material movement. The research emphasizes that mitigating carbon emissions in the construction industry requires a comprehensive approach encompassing technological advancements, logistical optimization, and the adoption of sustainable practices. By embracing the strategies highlighted in this study, construction projects can significantly contribute to the global fight against climate change and align with international efforts to achieve a more sustainable future. The insights provided by this research underscore the imperative for collaboration among stakeholders to drive meaningful change and foster a more sustainable and environmentally conscious construction industry.